If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b = (b + -4) + -1(5 + 3b) Reorder the terms: b = (-4 + b) + -1(5 + 3b) Remove parenthesis around (-4 + b) b = -4 + b + -1(5 + 3b) b = -4 + b + (5 * -1 + 3b * -1) b = -4 + b + (-5 + -3b) Reorder the terms: b = -4 + -5 + b + -3b Combine like terms: -4 + -5 = -9 b = -9 + b + -3b Combine like terms: b + -3b = -2b b = -9 + -2b Solving b = -9 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. b + 2b = -9 + -2b + 2b Combine like terms: b + 2b = 3b 3b = -9 + -2b + 2b Combine like terms: -2b + 2b = 0 3b = -9 + 0 3b = -9 Divide each side by '3'. b = -3 Simplifying b = -3
| 2X=X(1+0.087) | | a=2-(5+2a) | | 14x^2+3x=0 | | 64x-4x^2=0 | | y=(-10x^2)+50X | | 3t^2/5=t/5+7/12 | | 2X=X(1+0.087)N | | x^2/6+5x/6+1=0 | | 1/4(x+12)=9 | | x^2-8x=x(5+x) | | 5(2+x)=4x+17 | | x^2+4x-24= | | 3x+3=10x-80 | | 2x^2+(3a+4b)x=0 | | 2x^2+(3a+4b)x+a^2+3ab+2b^2=0 | | 2(2c-1)=4(3c-2) | | 4b^2-11ab+6a^2=0 | | 36r=12 | | 6a^2+ab-2b^2=0 | | 1/2x+1/4-1/x-1=x/2 | | 6x+2=4+18 | | 8x+33=27 | | b+6/4b2+3/2b2=b+4/2b2 | | M-2(1-3m)=6+3(4-m) | | 5x+14=16-10x | | 0.25(2x+1)-1/x-1=x/2 | | 4(x+1)2-2(2x-5)(x+2)=0 | | 15u^2+u-2=0 | | (x+3)-(2x-7)+6=13(x-1)+4(2x+1)-7x | | x+5/3-18-2x/4=x+3/6 | | (2k+5/4)=2-(k+2/3) | | (7k/4)=2-(2k/3) |